Minha trajetória no curso de medicina da UFSCar: reflexões, afetos e sentidos a partir da formação médica - Carvalho, Aline Augusto de (Universidade Federal de São Carlos, 2024)
Reflective narrative based on the trajectory of a medical student over 6 years in a course based on active learning methodology. The first years of the degree brought the challenge of adapting to the method in addition to the interruption of activities due to the COVID-19 pandemic in 2020. The course's approach has the potential to develop critical-reflective reasoning, with evidence-based and practical learning from the first year onwards, achieving humanized training, respect for the potential of each individual and the intellectual growth of its graduates.
My trajectory in the medicine course at UFSCar: reflections, affects and senses from medical training
Keywords: Medicine; Active learning; Narrative; CIENCIAS HUMANAS::EDUCACAO::CURRICULO